Financial management : principles and applications - Titman, Sheridan (Pearson series in finance, 2018)
The "10 Principles of Finance" formerly "Axioms" provide the framework, or "the big picture" of finance, which ties the major concepts of the book together. This text constitutes a strong basis on which to build future studies and, for those students who are non-finance majors, a lasting understanding in the fundamentals of finance.